Competência informacional e a busca de informações científicas: um estudo com pós-graduandos da Faculdade de Ciências Agronômicas da UNESP campus de Botucatu - Guerrero, Janaína Celoto [UNESP] (2009)
The research deals with the issue information literacy, specifically on the search for scientific information for graduate students in education post-graduation in Agricultural Sciences and Forestry Science, whose main objective is to verify the performance of graduate students in search of scientific information. Its specific objectives: a) develop an instrument to assess the information literacy of the participants in the search for scientific information, b) whether the participants know and use Boolean operators in developing search strategies, c) whether the participants are familiar with the development of search strategies, d) investigate how the participants tend to use sources of information for the development of research, e) raise subsidies for training programs for users of the Library of the Faculty of Agronomic Sciences, UNESP, Botucatu, that assist the development of information competencies. For data collection a questionnaire was elaborated based on information literacy standards for higher education developed by the Association of College and Research Libraries, American Library Association, and also in international research on the subject. The questionnaire was administered via the Internet to students of the Post-graduate degree in Agronomy and Forest Science, Faculty of Agronomic Sciences, UNESP, Botucatu. The results showed that students generally have difficulty in the use of Boolean operators, the development of search strategies and the use of search tools available, whether the databases or electronic catalogs. The inclusion of policies on skills in informational classes and courses taught by the Library can improve the performance of students in the use of information resources.